Moxifloxacin: safety profile - A. I. Sinopalnikov (Медицинский совет, 2013)
The latest, so-called respiratory, fluoroquinolones are a group of antimicrobial agents (AMA), most commonly prescribed for community-acquired lower respiratory tract infection (caLRTI), which is a relevant issue in routine clinical practice.